موقف الفقهاء فى اللفظ المشترك وأثره فى الفقه الإسلامي - Ahmad Sudirman Abbas (AHKAM : Jurnal Ilmu Syariah, 2016)
Lafzh musytarak (ambiguous word) is one literary study to produce a certain law. Such as the word “al-lams” which means touch of skin in the explicit sense and sexual activity of husband and wife in implicit sense. As a result, it has different consequences. If the interpretion of “al-lams” is touch of skin, the person should repeat his wudu’ (ablution). If the interpretion of “al-lams” is sexual activity of a couple, they have to take junub bath to purify them from large hadats. These two meanings have deep arguments based on religious scripture and in-depth research on any related word in several literature. This activity also needs to consider logical and relevant situation and condition to perfectly implement Sharia values.DOI: 10.15408/ajis.v16i1.2903